2020
DOI: 10.1016/j.eclinm.2020.100515
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection in the COPD population is associated with increased healthcare utilization: An analysis of Cleveland clinic's COVID-19 registry

Abstract: Background We sought to determine whether COPD conferred a higher risk for healthcare utilization in terms of hospitalization and clinical outcomes due to COVID-19. Methods A cohort study with covariate adjustment using multivariate logistic regression was conducted at the Cleveland Clinic Health System in Ohio and Florida. Symptomatic patients aged 35 years and older who were tested for SARS-CoV-2 between March 8 and May 13, 2020 were included. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 45 publications
3
56
0
1
Order By: Relevance
“…A recent report demonstrated that COPD is not a predisposing factor for SARS‐CoV‐2 infection, but once the patient develops the disease they have an elevated risk of hospitalization (aOR: 1.36), ICU admission (aOR: 1.20) and receiving invasive mechanical ventilation (aOR: 1.49) 18 . In a multicenter study including 476 COVID‐19 patients, the prevalence of COPD was found to be significantly different according to disease severity: lowest in the moderate group (2.3%), intermediate in the severe group (5.6%) and highest in the critically ill group (15.7%) 103 .…”
Section: Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report demonstrated that COPD is not a predisposing factor for SARS‐CoV‐2 infection, but once the patient develops the disease they have an elevated risk of hospitalization (aOR: 1.36), ICU admission (aOR: 1.20) and receiving invasive mechanical ventilation (aOR: 1.49) 18 . In a multicenter study including 476 COVID‐19 patients, the prevalence of COPD was found to be significantly different according to disease severity: lowest in the moderate group (2.3%), intermediate in the severe group (5.6%) and highest in the critically ill group (15.7%) 103 .…”
Section: Comorbiditiesmentioning
confidence: 99%
“…A good understanding of the possible risk factors in combination to disease immunopathology associated with COVID‐19 severity is helpful for clinicians in identifying patients who are at high risk and require prioritized treatment to prevent disease progression and adverse outcome 4 . Risk factors range from demographic factors, such as age, 3,5–7 sex and ethnicity, 8,9 diet and lifestyle habits 10,11 to underlying diseases 12–22 and complications, 23–26 and laboratory indications 27–39 . Many studies have reported predictive models using various risk factors to identify high‐risk patients that may develop severe and critical illness 40 .…”
Section: Introductionmentioning
confidence: 99%
“…Another cohort study with covariate adjustment using multivariate logistic regression revealed no significant differences in the rate of SARS-CoV-2 positivity between COPD and non-COPD patients. However, significantly higher rates of hospitalization [adjusted odds ratio [OR]of 1.36], ICU admissions (adjusted OR of 1.20), and invasive mechanical ventilation (adjusted OR of 1.49) were observed in COPD patients infected with the virus when compared with non-COPD patients ( 15 ).…”
Section: Covid-19 and Copd: Epidemiologymentioning
confidence: 99%
“…First, COPD patients often use many metered dose inhalant medications such as corticosteroids (ICS). The study by Attaway et al ( 15 ) showed that COPD patients who tested positive for SARS-CoV-2 were 2.4 times less likely to have used corticosteroids at the time of testing than those who tested negative. Notwithstanding a few significant methodological limitations, such as proper control for confounding factors including treatment indication and disease severity, they raise a question about corticosteroids' role in COVID-19.…”
Section: Aecopd and Covid-19mentioning
confidence: 99%
“…However, several other small cohort studies suggest a higher variation in the vulnerability of COPD patients to COVID-19 ranging from a low of 4 %- to as high as 38 % (Leung et al, 2020[ 9 ]). Attaway and colleagues (2020[ 2 ]), in their findings from a large cohort study of 15,586 symptomatic patients at the Cleveland Clinic COVID-19 registry, showed that 9.2 % of COVID patients had COPD but on adjustment for covariates, COPD was not found to be a risk factor for COVID-19. The low prevalence of COPD in this cohort indicates a superior study design by authors who prevented sampling bias, as they included only COPD patients and excluded patients with other chronic lung conditions (Sin, 2020[ 13 ]).…”
mentioning
confidence: 99%